Efektivitas metode latihan jarak jauh dengan kecepatan lambat dalam meningkatkan vo₂max pada atlet basket - Hermanto, Hermanto; Iqbal, Rahmat (Jurnal SPORTIF : Jurnal Penelitian Pembelajaran, 2025)
Basketball is a high-intensity sport that demands superior aerobic capacity to sustain performance throughout the match. One key physiological indicator of endurance is VO₂Max, which plays a crucial role in determining an athlete’s ability to recover and maintain performance. This study aims to examine the effectiveness of the Long Slow Distance (LSD) training method in enhancing the VO₂Max of male basketball athletes at Jakarta State University (UNJ). The research employed a pre-test and post-test experimental design with a single group. The LSD training intervention was conducted over a period of six weeks, with a frequency of three sessions per week, totaling 18 sessions. A total of 17 male basketball athletes were selected using total sampling from a population of 20 athletes. The Beep Test was selected as the primary VO₂Max assessment tool due to its practical application in field settings. Data analysis was conducted using SPSS software, applying tests for normality, homogeneity, and paired sample t-tests with a significance threshold of p ≤ 0.05. The paired sample t-test revealed a statistically significant improvement in VO₂Max (t(16) = 13.40, p < 0.001, Cohen’s d = 1.83), indicating a large effect size and meaningful physiological adaptation. Similarly, the Beep Test scores improved significantly (t(16) = 10.11, p < 0.001, Cohen’s d = 1.53), reflecting a substantial increase in aerobic endurance. These findings confirm that LSD training effectively improves aerobic capacity and serves as a suitable endurance strategy, particularly during the general preparatory phase, to support performance in high-intensity sports like basketball.